Answer:
x= -5, -1
Explanation:
To find the zeroes of a function,
First expand the terms to get the form
where 'a, b, and c' are constants
![f(x)= (x+3)^(2) -4](https://img.qammunity.org/2021/formulas/mathematics/college/zd3e9as4wymbeoxali1szh27qus0pa71eo.png)
![f(x)= x^(2)+6x+9-4](https://img.qammunity.org/2021/formulas/mathematics/college/wxd3pju017fq96yxotygwin49rx88t1uu9.png)
![f(x)= x^(2) +6x +5](https://img.qammunity.org/2021/formulas/mathematics/college/pfqmdvvn6om5xgi1d923gfrtrz4dn0tle9.png)
Now, factor the equation
This can be done using the quadratic formula or other methods
One simple method is to find the two values that would get:
- A sum that's equal to the 'b' value and,
- A product that's equal to the 'c' value
A good way to verify is to expand the terms and make sure the function looks the same
In this case, the equation can broken into
f(x)= (x+1)*(x+5)
Now, look at each term individually and set each of them to equal 0
x+1 =0
x+5=0
Solve for x in each case
x= -1
x= -5
Now, ordering them from least to greatest would be: x= -5, -1